Association between Functional Severity and Amputation Type with Rehabilitation Outcomes in Patients with Lower Limb Amputation. (21st October 2014) - Karmarkar, Amol M.; Graham, James E.; Reistetter, Timothy A.; Kumar, Amit; Mix, Jacqueline M.; Niewczyk, Paulette; Granger, Carl V.; Ottenbacher, Kenneth J.
Abstract : The purpose of this study was to determine independent influences of functional level and lower limb amputation type on inpatient rehabilitation outcomes. We conducted a secondary data analysis for patients with lower limb amputation who received inpatient medical rehabilitation ( N = 26, 501). The study outcomes included length of stay, discharge functional status, and community discharge. Predictors included the 3-level case mix group variable and a 4-category amputation variable. Age of the sample was 64.5 years (13.4) and 64% were male. More than 75% of patients had a dysvascular-related amputation. Patients with bilateral transfemoral amputations and higher functional severity experienced longest lengths of stay (average 13.7 days) and lowest functional rating at discharge (average 79.4). Likelihood of community discharge was significantly lower for those in more functionally severe patients but did not differ between amputation categories. Functional levels and amputation type are associated with rehabilitation outcomes in inpatient rehabilitation settings. Patients with transfemoral amputations and those in case mix group 1003 (admission motor score less than 36.25) generally experience poorer outcomes than those in other case mix groups. These relationships may be associated with other demographic and/or health factors, which should be explored in future research.